Formulation & Evaluation of Controlled Release Matrix Tablets of Fosinopril by Using Hydrophilic Polymer - Gopaiah, K. Venkata; Medarametla, Ramya Teja; Kumar, J. N. Suresh; Niharika, Kilari; Venkata Sai, Nelapati; Pavani, Vellaturi; Shaik Irfan, Jampakhanala; Manjula, Palavai (Journal of Neonatal Surgery, 2025)
The pre-formulation characteristics of Fosinopril were thoroughly assessed, including sensory attributes, angle of repose, bulk density, tapped density, Hausner’s ratio, Carr’s index, and compressibility index, all of which conformed to the required pharmacopeial standards. FTIR spectroscopy confirmed the absence of any significant interaction between the drug and the polymers. Controlled-release matrix tablets containing Fosinopril were formulated using HPMC K100 M and Xanthan gum as the primary polymers. The tablets underwent a series of evaluations, such as hardness, weight variation, and friability testing, with the majority of batches meeting the established pharmacopeial criteria. The drug content across different batches varied from 93% to 100%. Dissolution tests were performed in both acidic (pH 1.2) and phosphate buffers (pH 6.8), showing that the formulations with Xanthan gum released the drug more rapidly than those with HPMC. Importantly, the formulation combining both HPMC and Xanthan gum (F9) exhibited a significantly prolonged release profile over 24 hours, achieving a cumulative release of 99.74%. Kinetic analysis of F9 indicated a zero-order release pattern (regression coefficient 0.993) and anomalous non-Fickian diffusion (n > 5), suggesting a controlled-release mechanism. Stability studies conducted under accelerated conditions for 3 months showed no significant degradation, indicating that formulation F9 is optimal for sustained drug delivery. Further in vivo studies are necessary to confirm these results.